Penerapan Media Pembelajaran Powerpoint Dalam Meningkatkan Hasil Belajar Matematika di SMK Negeri 1 Aek Nabara Barumun - Nurhayati Pulungan; Nurdalilah; Susi Sulastri Lubis; Mohd. Arifin (Jurnal Cermatika, 2023)
The research method used was classroom action research using two cycles carried out in the first semester with SPLDV material. The sample in this research was 36 students in class X Office Automation and Management at SMK Negeri 1 Aek Nabara. The class used as a sample is class X Office Automation and Management at SMK Negeri 1 Aek Nabara which will use Power Point media in learning. The results of the research show that the ability of students' learning outcomes in learning Mathematics through the PowerPoint media learning model for class , then increased to 88.55 in the "Good" category in cycle II. The results obtained in cycle II showed that the expected categories had been fulfilled, namely with an average score of 75 and classical completion of 75% of students getting a minimum score of Good.